The Impact of the Educational Program on the Processing of Moringa Leaves and Mackerel Tuna for Stunting Prevention in Tongali Village - Thaifur, Andi Yaumil Bay R; Urufia, Wa Ode Nadziyran; Azis, Waode Azfari; Fitriani; Nurhidayati, Wa Ode; Subhan, Muhamad; Amiruddin, Eky Endriana; Dafid, Darsal Zulfakar (Jurnal Pangan Gizi dan Kesehatan, 2025)
Background: Stunting prevention can be accomplished by augmenting maternal knowledge through education that employs locally accessible nutrient-rich foods to facilitate children's growth and development. This entails converting moringa leaves into moringa cake and mackerel tuna into chips as nutritional snack alternatives and flavor enhancers to substitute MSG, thereby supporting the Free Nutritious Meal Program (MBG). Objectives: This study aimed to determine the impact of the educational program on the processing of moringa cake, tuna-based flavor enhancers, and mackerel tuna chips for stunting prevention toward the knowledge of the Family Welfare Movements (PKK) mothers in Tongali Village. Methods: The study used a quasi-experimental design. The sampling method used was accidental sampling, comprising a sample size of 40 respondents. Bivariate analysis was performed utilizing the One Group Pretest-Posttest Design with the Wilcoxon Signed Rank test. Results: Bivariate analysis demonstrated that the educational program significantly influenced the knowledge of PKK mothers before and after their implementation (Prob > |z| = 0.0000 < 0.05). Conclusions: This study aimed to enhance the engagement of PKK mothers in the utilization of moringa leaves and mackerel tuna for the preparation of nutritious foods, diminish the reliance on MSG to mitigate stunting, and bolster the local economy.